Antiparasitic activity of sulfur- and fluorine-containing bisphosphonates against trypanosomatids and apicomplexan parasites - Galaka, Tamila Pavlivna (2017)
Based on crystallographic data of the complexes 2-alkyl(amino)ethyl-1,1-bisphosphonates-Trypanosoma cruzi farnesyl diphosphate synthase, some linear 1,1-bisphosphonic acids and other closely related derivatives were designed, synthesized and biologically evaluated against T. cruzi, the responsible agent of Chagas disease and against Toxoplasma gondii, the etiologic agent of toxoplasmosis and also towards the target enzymes farnesyl pyrophosphate synthase of T. cruzi (TcFPPS) and T gondii (TgFPPS), respectively. The isoprenoid-containing 1,1-bisphosphonates exhibited modest antiparasitic activity, whereas the linear α-fluoro-2-alkyl(amino)ethyl-1,1-bisphosphonates were unexpectedly devoid of antiparasitic activity. In spite of not presenting efficient antiparasitic activity, these data turned out to be very important to establish a structural activity relationship.